Exporting and productivity: The role of ownership and innovation in the case of Vietnam - Carol Newman; John Rand; Finn Tarp; Nguyen Thi Tue Anh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this paper, we investigate the relationship between exporting and productivity in the case of Vietnam using an extensive firm level panel dataset for the period 2005-11. We separate out productivity effects of exporting due to self-selection allowing us to identify the extent to which firms learn-by-exporting. We examine the relationship between exporting and productivity in foreign-owned firms and private domestic firms separately and find the former benefit more from exporting, particularly wholly foreign-owned firms. Our analysis suggests that these effects are likely to be attributed to initial productivity improvements due to entry into export markets suggesting that the productivity gains are associated with the removal of local market constraints. We also find some evidence of productivity improvement for domestic firms associated with exporting. These effects can be attributed to within-firm innovations in production processes and product quality.
Keywords: D22; F14; O14; 330; learning by exporting; self-selection; productivity; Vietnam; firm ownership; innovation